Diversity of The Insect Visitors Species on Lily-Leaf Acriopsis Acriopsis liliifolia (J. Koenig) Ormerod in Ayunan Langit, Kalurahan Purwosari, Girimulyo, Kulon Progo - Aini, Lisna Nur; Sumarmi, Siti (Al-Kauniyah: Jurnal Biologi, 2025)
Besides being a microhabitat for insects, Acriopsis liliifolia orchid's economic value can be increased through cultivation techniques, but it is constrained because A. liliifolia flowers can't self-pollinate. Based on their flower structure, insects have the potential to become their pollinator. Insect visitors of A. liliifolia must be identified to know their species diversity and roles during visiting orchids. The research was conducted in Ayunan Langit, Sabrangkidul, Kalurahan Purwosari, Girimulyo, Kulon Progo from September to October 2023. Insect collection was done manually by brush and then put in a flask bottle containing 5 mL of 70% alcohol. The collected specimens were then carried out to the Entomology Laboratory, Faculty of Biology, Gadjah Mada University, and identified based on morphology characters. The results showed that there was one member of Cicadellidae and 14 species of insect visitors to the A. liliifolia. The majority of insect visitors acted as herbivores (73.33%), 20% as carnivores, and the rest is unknown. It is predicted that the Braunsapis genus is a pollinator because it has a tonguelike maxilla and labium used to suck nectar. In this study, we conclude that the diversity of insect visitor species in A. liliifolia is moderate (H’= 1.95) and Braunsapis has potential as a pollinators